Augmented Reality Marketing: Creating Immersive Brand Experiences - Salamatun Asakdiyah; Siti Amirah Makarim; Iwan Adinugroho (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research investigates the effects of augmented reality marketing on consumer behavior and brand perception within the context of Indofood Yogyakarta. Using a quantitative research design, a sample of 100 customers was randomly selected, and path analysis was conducted to examine the direct and indirect relationships between augmented reality, user engagement, user perception of innovation, and brand experience. The results indicate significant direct effects of augmented reality and user engagement on brand experience, highlighting the importance of augmented reality technology and consumer engagement in shaping positive brand experiences. Furthermore, the study reveals a significant indirect effect of augmented reality on brand experience through user perception of innovation, emphasizing the mediating role of consumers' perceptions of innovation. However, the indirect effect of user engagement on brand experience through user perception of innovation was nonsignificant, suggesting the need for further exploration of alternative pathways. These findings provide valuable insights for marketers aiming to enhance consumer engagement, satisfaction, and loyalty through augmented reality marketing strategies in Yogyakarta's competitive market landscape.